Wnt1-regulated genetic networks in midbrain dopaminergic neuron development - Wolfgang Wurst; Nilima Prakash (2013)
Neurons synthesizing the neurotransmitter dopamine exert crucial functions in the mammalian brain. The biggest and most important population of dopamine-synthesizing neurons is located in the mammalian ventral midbrain (VM), and controls and modulates the execution of motor, cognitive, affective, motivational, and rewarding behaviours. Degeneration of these neurons leads to motor deficits that are characteristic of Parkinson's disease, while their dysfunction is involved in the pathogenesis of psychiatric disorders including schizophrenia and addiction. Because the aetiology and therapeutic prospects for these diseases include neurodevelopmental aspects, substantial scientific interest has been focused on deciphering the mechanistic pathways that control the generation and survival of these neurons during embryonic development. Researches during the last decade revealed the pivotal role of the secreted Wnt1 ligand and its signalling cascade in the generation of the dopamine-synthesizing neurons in the mammalian VM. Here, we summarize the initial and more recent findings that have unravelled several Wnt1-controlled genetic networks required for the proliferation and commitment of VM progenitors to the dopaminergic cell fate during midgestational embryonic stages, and for the correct differentiation of these progenitors into postmitotic dopamine-synthesizing neurons at late midgestational embryonic and foetal stages.